1996
DOI: 10.1111/j.2044-8295.1996.tb02580.x
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and negative priming: Evidence for diminished cognitive inhibition in impulsive children

Abstract: This study addresses the relationship between impulsivity and lack of inhibition. Inhibition was measured bath by the interference score and by the negative priming effect in a Stroop colour-word paradigm. The negative priming effect in this paradigm is defÏned by slower naming of a target colour if this colour was the distractor in the immediately preceding trial.Por the study, a total of 210 school children were selected. These were children rated high or low by their teachers for either social or cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 28 publications
3
19
0
2
Order By: Relevance
“…For word Stroop tasks, similar to the classical paradigm, the differences are observed only when 7-8 years children are compared with children older than 9 years or adolescents. If the sample only includes children older than 9 years, the age effect is not observed 12,15,31,32 . These findings support the hypotheses that reading becomes automatic after 9 years of age and, because of that, interference scores increase and reach adult level 12,15,31,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For word Stroop tasks, similar to the classical paradigm, the differences are observed only when 7-8 years children are compared with children older than 9 years or adolescents. If the sample only includes children older than 9 years, the age effect is not observed 12,15,31,32 . These findings support the hypotheses that reading becomes automatic after 9 years of age and, because of that, interference scores increase and reach adult level 12,15,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…If the sample only includes children older than 9 years, the age effect is not observed 12,15,31,32 . These findings support the hypotheses that reading becomes automatic after 9 years of age and, because of that, interference scores increase and reach adult level 12,15,31,32 . In addition, when Stroop-like tasks without words were used, changes in susceptibility to interference were observed from 3 years of age, becoming more marked between 5 and 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to interpret the nature of these general deficits. If we refer to the existing literature that shows differences in cognitive functioning between obese and non-obese people (e.g., Nasser et al, 2004;Nederkoorn, Braet, et al, 2006), it could be argued that obese persons have a fundamental inhibition problem, corresponding to a high level of impulsivity (Horn, Dolan, Elliott, Deakin, & Woodruff, 2003;Stein, Hollander, DeCaria, & Trungold, 1991;Visser, Das-Smaal, & Kwakman, 1996;White et al, 1994). However, the modified shifting task does not allow one to characterize the precise nature of the inhibition deficit: it may be a deficit affecting prepotent response inhibition and/or a deficit affecting resistance to proactive interference (Friedman & Miyake, 2004).…”
mentioning
confidence: 99%
“…The finding of a more pronounced inhibition problem in obese persons with binge eating disorder is of crucial practical importance. Some authors have shown that impulsivity, which is related to inhibitory difficulties (Horn et al, 2003;Stein et al, 1991;Visser et al, 1996;White et al, 1994), predicts overeating (Guerrieri, Nederkoorn, & Jansen, 2007). This tendency to overeat can, in turn, lead to weight gain and to the development of maladaptive strategies to control weight (e.g., dieting, skipping meals).…”
mentioning
confidence: 99%
“…HI = high impulsiveness; LI = low impulsiveness; RTs = reaction times. ing that self-reported levels of impulsiveness in healthy individuals are not reflected in either inhibitory control as measured by Go/ Nogo (Fallgatter and Herrmann, 2001;Horn et al, 2003) or stopsignal tasks (Dimoska and Johnstone, 2007;Lansbergen et al, 2007), or in interference control as measured by the Stroop test (Visser et al, 1996;Avila and Parcet, 2001;Cheung et al, 2004;Kirkeby and Robinson, 2005). While self-report questionnaires measure different dimensions of trait impulsiveness, experimental tasks, such as the Go/Nogo or the stop-signal task, measure the prepotent response inhibition (Friedman and Miyake, 2004).…”
Section: Discussionmentioning
confidence: 97%